2021
DOI: 10.3390/min11111231
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Content in the Plants (Pleurozium schreberi and Picea abies) of Environmentally Important Protected Areas of the Tatra National Park (the Central Western Carpathians, Poland)

Abstract: This work concerns the content of selected heavy metals (Cd, Cr, Cu, Ni, Pb, and Zn), and determines the effect of absolute altitude on the content of metals in the plants of the Tatra National Park (TNP). The metals were determined in two species of plants, i.e., in the moss (Pleurozium schreberi (Willd.) Mitten) and in the Norway spruce (Picea abies (L.) H. Karst). Plant samples were collected in two test areas every 100 m of the altitude of the area, starting from 1000 m above sea level in the Lake Morskie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Due to the prolonged atmospheric dust, low pressure, and strong wind, heavy metals are displaced over considerable distances from emission sources [6,7]. This occurrence is observed, in particular, in mountainous areas, where plants and soil are contaminated with heavy metals despite the absence of sources of emissions of these metals in the immediate vicinity [8,9]. For research to observe the impact of long-range emissions on the size of the accumulation of heavy metals in soil, a mountainous area was selected [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the prolonged atmospheric dust, low pressure, and strong wind, heavy metals are displaced over considerable distances from emission sources [6,7]. This occurrence is observed, in particular, in mountainous areas, where plants and soil are contaminated with heavy metals despite the absence of sources of emissions of these metals in the immediate vicinity [8,9]. For research to observe the impact of long-range emissions on the size of the accumulation of heavy metals in soil, a mountainous area was selected [10].…”
Section: Introductionmentioning
confidence: 99%
“…Conifers are frequently used as bioaccumulators in environmental research. As a rule, they are evergreen and rarely deciduous trees that can bind pollutants from the air for several years in their assimilation apparatus [29]. Some studies have shown that fast-growing trees can accumulate more HM from the soil than from the atmosphere [30].…”
Section: Introductionmentioning
confidence: 99%